Implementasi Teknologi Pompa Air Tenaga Surya di Desa Karyabaru Kecamatan Barambai Kabupaten Barito Kuala - Abdul Rozaq; Muhammad Firdaus Jauhari; Raden Kelik Hardinto (Jurnal IMPACT: Implementation and Action, 2019)
The research and community service program in the Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Banjarmasin (Poliban) was prepared with reference to the application of science and technology that is able to provide appropriate solutions to problems, needs, and challenges in society. While community service activities focus on supporting efforts to improve community welfare and the competitiveness of universities. Based on the 2016-2021 RPJMD vision, the South Kalimantan province's medium-term regional development mission is set for 2016-2021, one of which reads "Developing regional infrastructure that supports the acceleration of economic and social cultural development". Based on the mission, the province of South Kalimantan must provide a solution to the issue of uneven infrastructure development problems. One of the solutions that can be implemented relates to the availability of clean water in rural areas with the program "Infrastructure Development to Meet the Health of the Clean Water of Rural Communities". The problems that arise in the implementation of the program are limited equipment, technology and science, therefore Poliban in this case the P3M tries to provide a solution to the problems that exist in the village of Karyabaru, Barambai sub-district, Barito Kuala District which is very short of clean water. The solution is to make a solar water pump in the village of Karyabaru, Barambai sub-district, Barito Kuala Regency. The community service programs were carried out in partnership with the Karyabaru and Karang Taruna Village Devices / Karyabaru Village Farmers Group. In order to guarantee the sustainability of the program that has been implemented later, it is then carried out assistance to the community so that all members of the community can participate in maintaining, caring for and implementing standards in the management of solar water pumps to meet clean water needs.